2013
DOI: 10.1080/00071668.2013.841861
|View full text |Cite
|
Sign up to set email alerts
|

Direct supplementation of diet is the most efficient way of enriching broiler meat with n-3 long-chain polyunsaturated fatty acids

Abstract: 1. Concentrations of beneficial omega-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFAs) in poultry meat can be improved by increasing the concentration of n-3 PUFA in poultry diets. 2. A decrease in flavour quality is, however, usually associated with the dietary supplementation with n-3 PUFA, which is due to the susceptibility of PUFA to oxidation. 3. This experiment was conducted to study the effects of introducing two different n-3 fatty acid sources (extruded linseed and DHA Gold™, a proprietary alga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 47 publications
9
50
1
1
Order By: Relevance
“…Although the yolk weights of the laid eggs were not significantly affected (see below), a reduced rate of hepatic VLDL secretion could result in more skipped days of egg production and account for the fewer eggs laid by hens fed the 40 g FLAX/kg diet because VLDL is the main yolk precursor macromolecule (Burley, Evans, & Pearson, 1993). It is well known that feeding chickens LNA, a competitive inhibitor of ALA metabolism, can attenuate the n-3 PUFA content of tissues and eggs (Fraeye et al, 2012;Jing et al, 2013;Ribeiro et al, 2013). The opposite also holds true for VLC n-6 PUFA, as demonstrated by the suppression of yolk ARA content and the elevation of yolk LNA content, by feeding hens increasing amounts of dietary FLAX (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the yolk weights of the laid eggs were not significantly affected (see below), a reduced rate of hepatic VLDL secretion could result in more skipped days of egg production and account for the fewer eggs laid by hens fed the 40 g FLAX/kg diet because VLDL is the main yolk precursor macromolecule (Burley, Evans, & Pearson, 1993). It is well known that feeding chickens LNA, a competitive inhibitor of ALA metabolism, can attenuate the n-3 PUFA content of tissues and eggs (Fraeye et al, 2012;Jing et al, 2013;Ribeiro et al, 2013). The opposite also holds true for VLC n-6 PUFA, as demonstrated by the suppression of yolk ARA content and the elevation of yolk LNA content, by feeding hens increasing amounts of dietary FLAX (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that feeding chickens LNA, a competitive inhibitor of ALA metabolism, can attenuate the n‐3 PUFA content of tissues and eggs (Fraeye et al, ; Jing et al, ; Ribeiro et al, ). The opposite also holds true for VLC n‐6 PUFA, as demonstrated by the suppression of yolk ARA content and the elevation of yolk LNA content, by feeding hens increasing amounts of dietary FLAX (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PLRP2 is absent in pigs, turkeys and ruminants but surprisingly present in horses (De Caro et al, 2008). This enzyme could potentially explain the high content of LNA deposition in horse tissues in comparison to porcine and poultry tissues (He, Ishikawa, & Hidari, 2005;Ribeiro et al, 2013). Based on the studies by Lorenzo, Fuciños, Purriños, and Franco (2010) and Guil-Guerrero et al (2013a) a large accumulation of LNA in horse tissues was evident when fed under extensive conditions (grass feeding) compared to animals finished with concentrates (3-5 kg/day for the last 3 months before slaughter (Table 2)).…”
Section: Digestive Physiology and Lipid Metabolism In Horsesmentioning
confidence: 94%
“…Thus, in the chicken, it is possible that exogenous (dietary) DHA and endogenous (biosynthesized) DHA exist in separate lipid pools in the hepatocyte, with one pool more "transportable" than the other. This would also explain why much greater muscle levels of DHA are attained when DHA is directly supplemented into the broilers' diet as a component of fish oil or algal oil (Leskanich and Noble, 1997;Gonzalez-Esquerra and Leeson, 2000;Rymer and Givens, 2006;Rymer et al, 2011;Ribeiro et al, 2013) as compared to having to be biosynthesized from ALA or SDA in the liver and exported to extra-hepatic tissues. However, it does not explain why more hepatically synthesized DPA than DHA is preferentially deposited into muscle in broilers fed ALA or ALA plus SDA (Tables 5 and 6; Betti et al, 2009;Kitessa and Young, 2009;Kartikasari et al, 2012;Baeza et al, 2013;Haug et al, 2014).…”
Section: Tablementioning
confidence: 96%